6-[(2E)-3,7-Dimethylocta-2,6-dien-1-yl]-5,7-dihydroxy-8-(2-methylbutanoyl)-4-phenyl-2H-chromen-2-one–6-[(2E)-3,7-dimethylocta-2,6-dien-1-yl]-5,7-dihydroxy-8-(3-methylbutanoyl)-4-phenyl-2H-chromen-2-one (1/1) from Mesua elegans - Awang, Khalijah; Chan, G.; Ismail, N.H.; Ng, Seik Weng; Tiekink, Edward R.T. (International Union of Crystallography, 2012)
The title co-crystal, C30H34O5·C30H34O5, comprises a 1:1 mixture of two mostly superimposed molecules with the same chemical formula that differ in the nature of the substituent (2-methylbutanoyl or 3-methylbutanoyl) bound at the exocyclic ketone. The lactone ring is close to planar (r.m.s. deviation = 0.058 Å) and the phenyl ring is twisted out of this plane [dihedral angle = 60.08 (9)°]. The geranyl substituent is almost normal to benzene ring to which it is connected [C—C—Car—Car (ar = aromatic) torsion angle = −87.8 (2)°]. Intramolecular O—H...O and O—H...π interactions are formed. In the crystal, supramolecular chains are formed along the a axis owing to C—H...O contacts, with the lactone carbonyl atom accepting two such bonds.